2020
DOI: 10.1021/acs.jnatprod.9b00470
|View full text |Cite
|
Sign up to set email alerts
|

Palhinosides A–H: Flavone Glucosidic Truxinate Esters with Neuroprotective Activities from Palhinhaea cernua

Abstract: Palhinosides A−H (1−8), new flavone glucosidic truxinate esters, including β-truxinate and μ-truxinate forms, were isolated from Palhinhaea cernua. Their structures were elucidated by extensive spectroscopic methods and chemical analyses. The flavone glucoside cyclodimers possess a unique cyclobutane ring in their carbon scaffolds. Compounds 2−7 represent three pairs of stereoisomers (2/3, 4/5, 6/7). The protective effects of 1−8 against the damage of HT-22 cells induced by L-glutamate were evaluated, and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Among the various substituted cyclobutanones, [7] significant research attention has been paid to the synthesis [8] and functionalization of 2substituted cyclobutanones. [4] The synthetic applications of 2substituted cyclobutanones also cover natural product synthesis. [9] In relation to the above-mentioned applications of 2-substituted cyclobutanones, it has been reported that 2alkylated cyclobutanones exhibit both cyto-and genotoxic properties under in vitro conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the various substituted cyclobutanones, [7] significant research attention has been paid to the synthesis [8] and functionalization of 2substituted cyclobutanones. [4] The synthetic applications of 2substituted cyclobutanones also cover natural product synthesis. [9] In relation to the above-mentioned applications of 2-substituted cyclobutanones, it has been reported that 2alkylated cyclobutanones exhibit both cyto-and genotoxic properties under in vitro conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The synthesis and various applications of substituted cyclobutanes have been the subject of several reviews. [2] The tetrasubstituted cyclobutane skeleton represents a key part of both katsumadain C [3] and the palhynosides A-H. [4] Moreover, substituted cyclobutane [5] and the cyclobutene [6] ring have been identified as constituents of the sesquiterpenes. Among the various substituted cyclobutanones, [7] significant research attention has been paid to the synthesis [8] and functionalization of 2substituted cyclobutanones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In addition, [2 + 2] cycloadducts of cinnamic acids are attractive synthetic targets because of their diverse and promising biological activity profiles and their presence in various natural products. 3 Irradiation of cinnamic acid derivatives in solution leads predominantly to E/Z photoisomerization, and therefore, efforts to achieve these transformations were focused primarily on solid-state photochemistry. 4 Early studies led to the topochemical reaction principles described by Schmidt for photochemical [2 + 2] cycloadditions in solid state.…”
mentioning
confidence: 99%